A Comparison of Endoscopic Ultrasound-Guided Fine-Needle Aspiration and Fine-Needle Biopsy in the Diagnosis of Solid Pancreatic Lesions - Lachlan R. Ayres; Elizabeth K. Kmiotek; Eric Lam; Jennifer J. Telford (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Endoscopic ultrasound (EUS) guided fine-needle aspiration (FNA) is the method of choice for sampling pancreatic lesions. This study compares the diagnostic accuracy and safety of FNB using a novel core needle to FNA in solid pancreatic lesions. Methods. A retrospective review of patients in whom EUS FNA or FNB was performed for solid pancreatic lesions was conducted. Diagnostic performance was calculated based upon a dual classification system: classification 1, only malignant pathology considered a true positive, versus classification 2, atypical, suspicious, and malignant pathology considered a true positive. Results. 43 patients underwent FNB compared with 51 FNA. Using classification 1, sensitivity was 74.0% versus 80.0%, specificity 100% versus 100%, and diagnostic accuracy 77.0% versus 80.0% for FNB versus FNA, respectively (all p>0.05). Using classification 2, sensitivity was 97% versus 94.0%, specificity 100% versus 100%, and diagnostic accuracy 98.0% versus 94.0% for FNB versus FNA, respectively (all p>0.05). FNB required significantly fewer needle passes (median = 2) compared to FNA (median = 3; p<0.001). Adverse events occurred in two (4.5%) FNB patients compared with none in the FNA group (p>0.05). Conclusion. FNA and FNB have comparable sensitivity and diagnostic accuracy. FNB required fewer passes.